A comparison of antibiotic use in three specialist paediatric hospitals in France, Latvia and the UK. Issue 3 (14th October 2014) - Sviestina, Inese; Aston, Jeff; Lorrot, Mathie; Mozgis, Dzintars
Abstract : Objectives: This article analyses antimicrobial use in three tertiary-care paediatric hospitals with the aim of improving antimicrobial stewardship in paediatric hospitals. Methods: A point prevalence survey (PPS) was undertaken during November 2012 using validated and standardised ARPEC (Antibiotic Resistance and Prescribing in European Children) methodology. The data collected contributed to the ARPEC study. Results: Antimicrobials were prescribed to 116 patients (48%) in Birmingham, 114 (38%) in Paris and 128 (37%) in Riga. Respiratory tract infections were the most common indications for antibiotic use in Riga, but in Birmingham and Paris antibiotics were used most for prophylaxis in case of medical problems. The most common age group of patients receiving antimicrobials across all three sites was children aged 1–5 years old: there were 41 (35%) children in this age group in Birmingham, 37 (32%) in Paris and 36 (28%) in Riga. The most common antimicrobial used for the treatment and prophylaxis of paediatric patients was co-trimoxazole in Birmingham and Paris and ceftriaxone in Riga. Antimicrobials were mainly used parenterally: there were 100 (55%) parenteral prescriptions in Birmingham, 122 (50%) in Paris and 111 (75%) in Riga. Conclusions: The PPS identified differences in antimicrobial use in the three hospitals and problem areas requiring improvement: high use of third-generation cephalosporins for paediatric patients (especially in Riga) and predominant use of parenteral antibiotics. Further collaboration between pharmacists operating at each site is needed in order to improve antimicrobial stewardship initiatives.